Two – photon excited fluorescence lifetime measurements through a double-clad photonic crystal fiber for tissue micro – endoscopy - Knorr, Florian (2011)
This paper presents an endoscopic configuration for measurements of tissue autofluorescence using two–photon excitation and time–correlated single photon counting detection through a double–clad photonic crystal fiber (DC–PCF) without pre-chirping of laser pulses. The instrument performance was evaluated by measurements of fluorescent standard dyes, biological fluorophores (collagen and elastin), and tissue specimens (muscle, cartilage, tendon). Current results demonstrate the ability of this system to accurately retrieve the fluorescence decay profile and lifetime of these samples. This simple setup, which offers larger penetration depth than one-photon-based techniques, may be combined with morphology-yielding techniques such as photoacoustic and ultrasound imaging.